Quality of superior mesenteric and hepatic artery dissection in robotic pancreatoduodenectomy for pancreatic cancer. (11th August 2022) - Ikoma, Naruhiko; Seo, Yongwoo D.; Newhook, Timothy E.; Maxwell, Jessica E.; Kim, Michael P.; Tran Cao, Hop S.; Tzeng, Ching‐Wei D.; Chun, Yun Shin; Lee, Jeffrey E.; Vauthey, Jean‐Nicolas; Katz, Matthew H. G.
Abstract : This video manuscript by Ikoma and colleagues demonstrates their approach to the superior mesenteric artery and hepatic artery periadventitial dissection. The quality of superior mesenteric artery and hepatic artery dissections should be maintained in robotic pancreatoduodenectomy when performed for pancreatic cancer, to provide the best possible oncological outcomes.